Risk of pregnancy and teenage sexual activity - Prior, Carlos (2001)
Objectives: To know the age of first full sexual intercourse, knowledge of the defined age group on contraception and sexuality, prevalence of sexual practices entailing risk of pregnancy, as well to know which are the variables that influence knowledge and sexual practices entailing risk of pregnancy. Type of Study: Descriptive, cross-sectional. Site: Fernão de Magalhães Health Centre in Coimbra. Population: Adolescents from the health centres roster, aged between 14 and 19 years on October 31st. Methods: A stratified, randomised sample of 346 subjects was taken out of a total of 3120 adolescents, proportionally to sex, age and health centre outpost roster dimension. The following variables were studied: sex, age, age at time of first sexual intercourse, marital status, occupation, degree of schooling, parents literacy level, sexual practices, school or work adaptation, family APGAR score, partnership relation, knowledge on contraception and sexuality, and sexual behaviours entailing risk of pregnancy. Results: 268 adolescents (77%) answered the questionnaire. One third had had full sexual intercourse. Only one third had «good» or «very good» knowledge on contraception and sexuality. The level of knowledge was higher among older teenagers, females, and youths belonging to dysfunctional families. Fourteen percent revealed sexual practices entailing risk of pregnancy; this increased with age, and decreased with the adolescents knowledge level and their parents literacy. Conclusions: These data showed a low level of knowledge and a high proportion of youths engaging in full sexual intercourse. This, together with the age at time of first sexual intercourse, makes it urgent to implement specific health education strategies for this age group.